Pengaruh Susu Kedelai dan Bubur Kacang Hijau terhadap Lingkar Pinggang Wanita Pascamenopause - Fendie K. Syailawan; Budiyanti Wiboworini; Lilik Retna Kartikasari (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Postmenopausal women are prone to obesity. Soy milk and mung bean porridge contain fiber andflavonoids which are beneficial as anti-obesity. This study aimed to analyze the effect of soy milk and mungbean porridge on waist circumference among postmenopausal women. This was an experimental study usingpre-posttest with the control group. The study was conducted for 4 weeks from December 2018 to January2019 in Serengan, Surakarta. Subjects were randomly divided into control group (n=10), soy milk (n=10) andcombination of soy milk and mung bean porridge (n=10). Soy milk and mung bean porridge provided were 240ml and 180 ml/day/person and given for 4 weeks, respectively. Data were then analyzed with paired t-test, oneway ANOVA and Bonferroni test. There were no significant differences in the nutritional status, occupation andeducation level of the three groups. There was a significant reduction in waist circumference in both the soymilk and combination group compared to the control group (p<0.05). The mean decrease in waist cirumferencewas -2.40±2.23 cm in the soy milk group and -5.30±3.20 cm in the combination group. Soy milk and mungbean porridge can be alternative therapies to reduce waist circumference among postmenopausal women.